1998
DOI: 10.1089/aid.1998.14.51
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Subtypes of HIV Type 1 and HIV Type 2 Strains in Commercial Sex Workers from Bamako, Mali

Abstract: In Africa the highest HIV infection rate has been reported among female commercial sex workers (CSWs) who are at increasing risk of acquiring and transmitting HIV infection. In October 1995, 176 CSWs were studied in Bamako, the capital city of Mali. The ages of the CSWs ranged from 15 to 50 years old (mean, 28.8 years). Only 20.45% of the 176 CSWs were Malian; the majority were from Nigeria (32.9%) and Ghana (31.8%), and the remaining were from other African countries. Forty-one percent were active for less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 26 publications
4
25
0
1
Order By: Relevance
“…Serology does not differentiate between cross-reactivity of antibody from an HIV-1 infected subject with HIV-2 antigens (or the reverse) and antibody response both to HIV-1 and HIV-2 (double infection). In addition, poorly sensitive PCR, might not be able to amplify HIV-1 or HIV-2 in double reactive samples [Peeters et al, 1998;Sagoe et al, 1999;Esteves et al, 2000]. In the present study, gag primers were designed to amplify both HIV-1 and HIV-2, env primers to amplify HIV-1 only and LTR primers HIV-2 only ].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Serology does not differentiate between cross-reactivity of antibody from an HIV-1 infected subject with HIV-2 antigens (or the reverse) and antibody response both to HIV-1 and HIV-2 (double infection). In addition, poorly sensitive PCR, might not be able to amplify HIV-1 or HIV-2 in double reactive samples [Peeters et al, 1998;Sagoe et al, 1999;Esteves et al, 2000]. In the present study, gag primers were designed to amplify both HIV-1 and HIV-2, env primers to amplify HIV-1 only and LTR primers HIV-2 only ].…”
Section: Discussionmentioning
confidence: 96%
“…As soon as it was fully analysed its mosaic structure became clear, with alternating A and G segments [Carr et al, 1998]. Mostly on the basis of partial genome sequencing, subtypes A, D, and G have been reported frequently as the most prevalent subtypes in West Africa [Ishikawa et al, 1996;Peeters et al, 1998;Davies et al, 1999;Sarr et al, 2000]. With the characterisation of CRF02_AG, phylogenetic analysis allowed to differentiate pure A and G subtypes from IbNg-related strains, leading to the conclusion that CRF02_AG and its recombinants represented the most prevalent HIV-1 strains in West Africa at present.…”
Section: Introductionmentioning
confidence: 99%
“…Guinea-Bissau has the highest HIV-2 prevalence worldwide (8 %-10 % in the general adult population) [2][3][4]. In recent years a decline in the prevalence of HIV-2 has been observed in most populations in West Africa including some communities in Guinea-Bissau [5][6][7]. HIV-2 prevalence decreased in men but not in women in a community study from urban Guinea-Bissau between 1987 and 1996 [8].…”
Section: Introductionmentioning
confidence: 99%
“…Among the pathogenetic mechanisms contributing to the lower virulence of HIV-2, a reduced functionality of its nef regulatory gene [Switzer et al, 1998] and a low infectious virus level in infected individuals, have been suggested [Simon et al, 1993]. Six different genetic subtypes of HIV-2 (A-F) have been recognized so far, HIV-2 subtype A being the most predominant [Gao et al, 1994;Chen et al, 1997;Takehisa et al, 1997;Peeters et al, 1998]. Lower or even lack of pathogenicity have been suggested for non-A subtypes [Gao et al, 1994].…”
Section: Introductionmentioning
confidence: 99%